Pemeriksaan Gula Darah Sewaktu pada Lansia di Posyandu Srikandi II Desa Loram Wetan - Budi Setiawan, Avi; Kusuma Raharja, Romadhlona Novadianto; Amanda Sekar Rahmadany; Krisna Bayu, Andre; Fathurrahman, Akmal (Universitas Negeri Semarang, 2025)
Glucose is one of the important sources of energy in the body. To know the glucose level in the human body, it can be known through a glucose test. The purpose of checking the blood sugar test is one of the anticipations of contracting the chronic disease Diabetes Mellitus, especially for the elderly. The Timed Blood Sugar test method was a strip method. The blood sugar test uses participant blood samples which will then be tested for glucose levels on the glucose meter. There were around 30 participants who took the blood sugar test. The results of the Blood Sugar Test showed that 8 out of 10 male were ≤ 200 mg/dl with 2 of them in the range of ≥ 200 mg/dl. While the results of the examination of 20 women showed that 15 were in the range of ≤ 200 mg/dl and 5 of them were in the range of ≥ 200 mg/dl. It can be concluded that there are 7 out of 30 participants who are in a condition of high blood sugar levels.